Comparative Diagnostic Performance of Monoclonal Antibody Immunohistochemistry and Modified Giemsa Staining for Helicobacter pylori Detection in Chronic Gastritis - Amalia Amalia; Upik A. Miskad; Zaldi Zaldi; Gina Andyka Hutasoit; Muhammad Aslam (Media Publikasi Cendekia Indonesia, 2026)
Accurate detection of Helicobacter pylori is essential for the effective management of chronic gastritis. While Modified Giemsa (MG) staining is a common diagnostic tool, its sensitivity can be limited in cases with low bacterial density or atypical morphology, often leading to under-detection. This study aimed to evaluate the comparative diagnostic performance and bacterial density grading of monoclonal antibody immunohistochemistry (IHC) versus MG staining to establish a more precise diagnostic algorithm. This analytical observational study utilized a retrospective cross-sectional design, analyzing 100 gastric biopsy specimens from patients with chronic gastritis. Detection rates and bacterial density, graded according to the Updated Sydney System, were compared between MG and IHC using monoclonal anti-H. pylori antibodies. Monoclonal antibody IHC demonstrated a significantly higher detection rate (72%) compared to MG (65%; p = 0.016). Discordance analysis identified seven cases that were positive by IHC but missed by MG, typically representing low-density infections. Although overall inter-method agreement was